Bendi : Transportasi Budaya di Kota Solok Sumatera Barat Antara Tantangan dan Peluang Tahun 1970-2000 - Yefriza, Mila; Ardhana, I Ketut; Wahyuni, Anak Agung Ayu Rai (Humanis, 2020)
This study has discussed about the existence of traditional transportation in the Solok city in 1970 or it's called bendi transportation. Bendi is a traditional transportation which still existed until 2000 in the middle of more sophisticated transportation in that era. This study has three problems to be discussed, they are (1) Why the bendi transportation still existed in the Solok, West Sumatra? (2) What are the challenges of bendi tansportation as traditional transportation in the Solok, West Sumatra? (3) What are the role of government in it?. This study used city's historical method and theory of history and social science by Wellman and Wortley in a modern sociology by George Ritzer were applied. The results of this study reveals thatbendi isa traditional transportation which still existed in the Solok, it’s describes the challenges of bendi as traditional transportation, and explains how the government plays a role in maintaining and preserving bendi as a traditional transportation asset in Solok, West Sumatra.